2010
DOI: 10.1080/10440041003680312
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agriculture: Teacher Beliefs and Topics Taught

Abstract: Sustainable agriculture (SA) is not fully understood. What is being taught about SA by high school agriculture teachers is also unclear. The purpose of this study was to identify the beliefs of high school agriculture teachers about SA and to examine the extent they teach SA. A mailed questionnaire was used to collect data from a random sample of 844 teachers in the North Central Region (NCR) of the United States. Teachers agreed to concepts about SA and taught selected SA topics to a moderate extent, emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…The distribution of the above research variables was generally normal, as is evident from the close approximation between each value of mean and median. Details of the results are reported elsewhere (Muma et al 2010). Table 3 presents the means, modes, and standard deviations for the demographics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of the above research variables was generally normal, as is evident from the close approximation between each value of mean and median. Details of the results are reported elsewhere (Muma et al 2010). Table 3 presents the means, modes, and standard deviations for the demographics.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mean scores for various demographics with continuous values were relatively high, the modal values for the demographics were zero or five years, contradicting the higher mean values. Table 4 presents frequencies and percentages by category for the demographic variables (Muma et al 2010). Twenty percent of the teachers had the least experience (of five years) regarding teaching about agriculture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we wanted to speak with different kinds of people-enough different kinds that a full range of opinions would emerge through in-depth interviews and subsequent analysis of language patterns in the transcripts. In addition to farmers, some scholars have widened their scope to include other stakeholders such as researchers (Wilkins et al, 2001), extension personnel and educators (Camara, Martin, and Kwaw-Mensah, 2009;Muma, Martin, and Shelley 2010;Rodriguez et al, 2008), and consumers (Pelletier, Kraak, McCullum, and Uusitalo, 2000;Hassanein, 2008;Schneider and Francis, 2006;Stock, 2007). Such investigations are important in part because studies have confirmed that community support-or lack of it-can play a key role in farmers' decisions to adopt and maintain sustainable practices (Morton and Weng, 2009;Guptill, 2009;Rodriguez et al, 2008;Burton, 2004;Hanson, Kauffman, and Schauer, 1996).…”
Section: Introductionmentioning
confidence: 93%
“…what subject matter is and is not included, also informs how they approach instruction (Muma, Martin, Shelley, & Holmes, 2010) and how they respond to curriculum change (Paecther, 2003).…”
Section: Beliefs About Content Teacher Beliefs About Their Particulamentioning
confidence: 99%